সরকার সংবিধান ও অধিকার - রহমান, মুহাম্মদ হাবিবুর (ঢাকা : সময় প্রকাশন, 1999)
On government, constitutional law, and fundamental rights with reference to Bangladesh.
Includes index.
In Bengali.
Keywords: Constitutional law -- Bangladesh; Civil rights -- Bangladesh; Bangladesh -- Politics and government -- 1971-